The Mechanisms and Management of Age-Related Oxidative Stress in Male Hypogonadism Associated with Non-communicable Chronic Disease - Leisegang, Kristian; Roychoudhury, Shubhadeep; Slama, Petr; Finelli, Renata (Antioxidants (Basel, Switzerland), 2021)
Androgens have diverse functions in muscle physiology, lean body mass, the regulation of adipose tissue, bone density, neurocognitive regulation, and spermatogenesis, the male reproductive and sexual function. Male hypogonadism, characterized by reduced testosterone, is commonly seen in ageing males, and has a complex relationship as a risk factor and a comorbidity in age-related noncommunicable chronic diseases (NCDs), such as obesity, metabolic syndrome, type 2 diabetes, and malignancy. Oxidative stress, as a significant contributor to the ageing process, is a common feature between ageing and NCDs, and the related comorbidities, including hypertension, dyslipidemia, hyperglycemia, hyperinsulinemia, and chronic inflammation. Oxidative stress may also be a mediator of hypogonadism in males. Consequently, the management of oxidative stress may represent a novel therapeutic approach in this context. Therefore, this narrative review aims to discuss the mechanisms of age-related oxidative stress in male hypogonadism associated with NCDs and discusses current and potential approaches for the clinical management of these patients, which may include conventional hormone replacement therapy, nutrition and lifestyle changes, adherence to the optimal body mass index, and dietary antioxidant supplementation and/or phytomedicines.
Keywords: testosterone; phytonutrients; noncommunicable chronic disease; nutrition; testosterone replacement therapy; antioxidants